2012
DOI: 10.1038/jhg.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphisms in the RET-protooncogene and NRG1 with Hirschsprung disease in Thai patients

Abstract: Hirschsprung disease (HSCR) is a congenital developmental defect of the enteric nervous system known to be associated with the RET-protooncogene and other candidates. Recently, a genome-wide association study has added NRG1, a regulator of the development of the enteric ganglia precursors, as a new candidate gene. The aim of this study is to validate the association of the RET-protooncogene and the NRG1 in HSCR in Thai patients. The study used TaqMan single-nucleotide polymorphism (SNP) genotyping and PCR-rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 27 publications
3
47
1
Order By: Relevance
“…These authors also demonstrated significant statistical evidence of genetic interaction between the RET rs2435357 and NRG1 rs7835688 variants, increasing the overall risk a further 2.3-fold, specifically in the presence of RET TT and NRG1 CG genotypes. Other authors have also reported genetic interactions between RET and NRG1 for both rare [10] and common [11] variants although the statistical significance of these findings is true only for common variants. These results are reminiscent of the individually strong genetic effects and interactions between loss-of-function alleles at RET and EDNRB , the two major signaling pathways important to enteric nervous system (ENS) development [12].…”
mentioning
confidence: 99%
“…These authors also demonstrated significant statistical evidence of genetic interaction between the RET rs2435357 and NRG1 rs7835688 variants, increasing the overall risk a further 2.3-fold, specifically in the presence of RET TT and NRG1 CG genotypes. Other authors have also reported genetic interactions between RET and NRG1 for both rare [10] and common [11] variants although the statistical significance of these findings is true only for common variants. These results are reminiscent of the individually strong genetic effects and interactions between loss-of-function alleles at RET and EDNRB , the two major signaling pathways important to enteric nervous system (ENS) development [12].…”
mentioning
confidence: 99%
“…Interestingly, the frequency of this NRG1 rare variant found in Indonesian [1/54 (1.8%) patients] was similar to those of Caucasian and Chinese probands [3/207 (1.4%) and 13/358 (3.6%) patients, respectively; with p  = 0.45] [10, 11]. Furthermore, the NRG1 rs7835688 common variant was originally associated with HSCR in Chinese patients [9] and has been similarly observed in other Asian ancestry cases [4, 27], but these associations were not replicated in any Caucasian population [11, 28]. …”
Section: Discussionmentioning
confidence: 56%
“…Although there have been previous studies correlating NRG1 SNPs with disease association in HSCR, these have only been reported in three populations, namely Chinese, Caucasian, and Thais [10, 11, 27, 28]. Indeed, contrary to the findings in Chinese, Luzón-Toro et al [11] failed to find association of NRG1 variants with HSCR phenotype in Spanish patients and suggested that this could be due to population differences.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Genotype determination of the SNP rs16754, a synonymous SNP within exon 7, was performed using the TaqMan SNP genotyping system (Applied Biosystems, Foster City, CA, USA) ( Table I). The details of this method were previously reported (23). The assay mixes, including unlabeled polymerase chain reaction (PCR) primers, carboxyfluorescein (FAM) and VIC dye-labeled TaqMan minor groove binder probes of the Assays-by-Design system, were designed by Applied Biosystems.…”
Section: Patients and Controlsmentioning
confidence: 99%